Assessing the performance of clinoptilolite for controlling and releasing ammonium in agricultural applications. (November 2021) - Wang, Yanzhi; Sun, Yidi; Chen, Hongyang; Wu, Qi; Chi, Daocai
Abstract: To develop soil holding capacity of NH 4 + and reduce the energy consumption of industrial fertilizer production, different dosages of clinoptilolite mixed with soil were used to absorb NH 4 +, which was also simulated using Freundlich and Langmuir equation under different conditions. The results showed that NH 4 + adsorption of clinoptilolite-amended soil changed from multilayer adsorption to single-layer adsorption with the increase in clinoptilolite application rates. The optimal ratio of clinoptilolite applied to the soil for high adsorption efficiency was 0.01g 10g −1 . The co-existence of Na + and K + increased the NH 4 + adsorption capacity of clinoptilolite-amended soil relative to the existence of single Na + . This showed that K + was less competitive towards NH 4 + than Na + . Decreasing water quantity, which increased the total soil adsorption capacity by a factor of 2 to 3, had the most significant effect and helped regulate the release of nitrogen in clinoptilolite-amended soil. In sum, clinoptilolite can enhance soil nitrogen holding capacity, which shows great potentials to reduce the energy consumption of industrial urea production.